Consecutive interactions with HSP90 and eEF1A underlie a functional maturation and storage pathway of AID in the cytoplasm - Methot, Stephen P. (J Exp Med, 2015)
Activation-induced deaminase (AID) initiates mutagenic pathways to diversify the antibody genes during immune responses. The access of AID to the nucleus is limited by CRM1-mediated nuclear export and by an uncharacterized mechanism of cytoplasmic retention. Here, we define a conformational motif in AID that dictates its cytoplasmic retention and demonstrate that the translation elongation factor eukaryotic elongation factor 1 α (eEF1A) is necessary for AID cytoplasmic sequestering. The mechanism is independent of protein synthesis but dependent on a tRNA-free form of eEF1A. Inhibiting eEF1A prevents the interaction with AID, which accumulates in the nucleus and increases class switch recombination as well as chromosomal translocation byproducts. Most AID is associated to unspecified cytoplasmic complexes. We find that the interactions of AID with eEF1A and heat-shock protein 90 kD (HSP90) are inversely correlated. Despite both interactions stabilizing AID, the nature of the AID fractions associated with HSP90 or eEF1A are different, defining two complexes that sequentially produce and store functional AID in the cytoplasm. In addition, nuclear export and cytoplasmic retention cooperate to exclude AID from the nucleus but might not be functionally equivalent. Our results elucidate the molecular basis of AID cytoplasmic retention, define its functional relevance and distinguish it from other mechanisms regulating AID.